Analisis Strategi Kampanye Pasangan Incumbent Lalu Pathul Bahri dan Muhammad Nursiah dalam Pilkada Lombok Tengah 2024 - St. Yulaiha; Rossi Maunofa Widayat (REFORM : Jurnal Pendidikan, Sosial, dan Budaya, 2025)
This study discusses the campaign strategy of the incumbent pair Lalu Pathul Bahri and Muhammad Nursiah in the 2024 Central Lombok election. The main objective of this study is how the political strategy of the campaign team can access various voter segments, especially the millennial and generation Z generations, through the use of social media. In addition, a direct approach to the community through a door-to-door strategy in building emotional closeness and increasing public trust.